Auto-Refining 3D Mesh Reconstruction Algorithm from Limited Angle Depth Data - Kulikajevas, Audrius; Maskeliunas, Rytis; Damasevicius, Robertas; Krilavicius, Tomas (IEEE access, 2022)
Despite 3D object reconstruction using a single perspective being a rapidly developing field, the majority of research is focused around a single static object reconstruction from a synthetically generated dataset. This leaves a major knowledge gap when it comes to morphing 3D object reconstruction from an imperfect real world frame. As a solution to this problem, we introduce a three-staged deep auto-refining adversarial neural network architecture that can denoise and refine real-world depth sensor data captured using Intel Realsense devices for a full human body posture reconstruction. The proposed solution was able to achieve results which are on par with other state-of-the-art approaches in both Earth Mover's and Chamfer distances, 0.059 and 0.079 respectively, while having the benefit of reconstructing from mask-less real world depth frames.With visual inspection of the reconstructed point-cloud suggesting great adaptation capabilities to the majority of real world depth sensor noise deformities for both LiDAR and structured light depth sensors.